2017
DOI: 10.1038/ncomms14868
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion/dilution enhances phytoplankton blooms in low-nutrient waters

Abstract: Spatial characteristics of phytoplankton blooms often reflect the horizontal transport properties of the oceanic turbulent flow in which they are embedded. Classically, bloom response to horizontal stirring is regarded in terms of generation of patchiness following large-scale bloom initiation. Here, using satellite observations from the North Pacific Subtropical Gyre and a simple ecosystem model, we show that the opposite scenario of turbulence dispersing and diluting fine-scale (∼1–100 km) nutrient-enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…One caveat for this study is the relatively weak local interannual correlations between our various physical metrics and biomass ( Figure S6), despite strong correlations on seasonal time scales (Cabre et al 2016). This discrepancy has been recently discussed in other recent studies (e.g., Dave & Lozier, 2013;Lozier et al, 2011), suggesting that other factors not addressed here may play a role in the observed interannual correlations and trends, that is, advection of nutrients from the subpolar to the subtropical gyres, or mesoscale eddy dynamics (Ayers & Lozier, 2010;Dufois et al, 2016;Lehahn et al, 2017;Palter et al, 2005) and changes in the grazing pressure (Boss & Behrenfeld, 2010).…”
Section: Discussionmentioning
confidence: 43%
“…One caveat for this study is the relatively weak local interannual correlations between our various physical metrics and biomass ( Figure S6), despite strong correlations on seasonal time scales (Cabre et al 2016). This discrepancy has been recently discussed in other recent studies (e.g., Dave & Lozier, 2013;Lozier et al, 2011), suggesting that other factors not addressed here may play a role in the observed interannual correlations and trends, that is, advection of nutrients from the subpolar to the subtropical gyres, or mesoscale eddy dynamics (Ayers & Lozier, 2010;Dufois et al, 2016;Lehahn et al, 2017;Palter et al, 2005) and changes in the grazing pressure (Boss & Behrenfeld, 2010).…”
Section: Discussionmentioning
confidence: 43%
“…d'Ovidio et al () suggested that horizontal stirring at the front can stretch large‐scale CHL patches into submesoscale CHL patches. Lehahn et al () showed that horizontal stirring is able to decrease the encounter rates of phytoplankton and zooplankton and consequently reduce grazing pressure on phytoplankton in the North Pacific subtropical gyre. Nevertheless, distinguishing these submesoscale frontal mechanisms in relation to high CHL requires interdisciplinary sampling programs (Lévy et al, ), which is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, an intense secondary circulation emerges across the front and increases the supply of nutrients and CHL along the edge of the eddy (Lévy & Martin, ; Mahadevan, ). Submesoscale processes may also shape filaments of CHL by simply stirring/advecting existing mesoscale patches of CHL (d'Ovidio et al, ) or by reducing grazing pressure and subsequently enhancing phytoplankton biomass (Lehahn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The images show snapshots from the evolution of patches. These studies quantified the structuring effect of horizontal stirring by comparing the morphology of the patches with spatial distribution patterns of synthetic particles advected by the surface currents (see data patches of high chlorophyll concentrations (Toner et al 2003;Lehahn et al 2007Lehahn et al , 2017Calil et al 2011;Huhn et al 2012;Efrati et al 2013;d'Ovidio et al 2015) (see Figures 3 and 4).…”
Section: Figurementioning
confidence: 99%